TCR triggering induces the formation of Lck-RACK1-actinin-1 multiprotein network affecting Lck redistribution - Ondrej Ballek (Frontiers in Immunology, 2016)
The initiation of T-cell signaling is critically dependent on the function of the member of Src family tyrosine kinases (SFKs), Lck. Upon TCR triggering, Lck kinase activity induces the nucleation of signal-transducing hubs that regulate the formation of complex signaling network and cytoskeletal rearrangement. In addition, the delivery of Lck function requires rapid and targeted membrane redistribution, but the mechanism underpinning this process is largely unknown. To gain insight into this process, we considered previously described proteins that could assist in this process via their capacity to interact with kinases and regulate their intracellular translocations. An adaptor protein, Receptor for Activated C Kinase 1 (RACK1), was chosen as a viable option and its capacity to bind Lck and aid the process of activation-induced redistribution of Lck was assessed. Our microscopic observation showed that T-cell activation induces a rapid, concomitant and transient co-redistribution of Lck and RACK1 into the forming immunological synapse. Consistent with this observation, the formation of transient RACK1-Lck complexes were detectable in primary CD4+ T-cells with their maximum levels peaking 10 seconds after TCR-CD4 co-aggregation. Moreover, RACK1 preferentially binds to a pool of kinase active pY394Lck which co-purifies with high molecular weight cellular fractions. The formation of RACK1-Lck complexes depends on functional SH2 and SH3 domains of Lck and includes several other signaling and cytoskeletal elements that transiently bind the complex. Notably, the F-actin-crosslinking protein, α-actinin-1, binds to RACK1 only in the presence of kinase active Lck suggesting that the formation of RACK1-pY394Lck-α-actinin-1 complex serves as a signal module coupling actin cytoskeleton bundling with productive TCR/CD4 triggering. In addition, the treatment of CD4+ T-cells with nocodazole, which disrupts the microtubular network, also blocked the formation of RACK1-Lck complexes. Importantly, activation-induced Lck redistribution was diminished in primary CD4+ T-cells by an adenoviral-mediated knock-down of RACK1. These results demonstrate that in T cells, RACK1 as an essential component of the multiprotein complex which upon TCR engagement links the binding of kinase active Lck to elements of the cytoskeletal network and affects the subcellular redistribution of Lck.